2023
DOI: 10.1038/s41598-022-27047-4
|View full text |Cite
|
Sign up to set email alerts
|

A nested bistable module within a negative feedback loop ensures different types of oscillations in signaling systems

Abstract: In this article, we consider a double phosphorylation cycle, a ubiquitous signaling component, having the ability to display bistability, a behavior strongly related to the existence of positive feedback loops. If this component is connected to other signaling elements, it very likely undergoes some sort of protein–protein interaction. In several cases, these interactions result in a non-explicit negative feedback effect, leading to interlinked positive and negative feedbacks. This combination was studied in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
0
1
0
Order By: Relevance
“…The parameter set we chose comes from our previous work ( Marrone et al, 2023 ), where the DP cycle displayed bistability when scanning the input kinase. This was a necessary condition to obtain oscillations in the motifs studied and valuable for this work since the presence of oscillations in the model and bistability in each of the two modules (emergent through SN or fold bifurcations) will test the pseudo-nullclines method.…”
Section: Resultsmentioning
confidence: 99%
“…The parameter set we chose comes from our previous work ( Marrone et al, 2023 ), where the DP cycle displayed bistability when scanning the input kinase. This was a necessary condition to obtain oscillations in the motifs studied and valuable for this work since the presence of oscillations in the model and bistability in each of the two modules (emergent through SN or fold bifurcations) will test the pseudo-nullclines method.…”
Section: Resultsmentioning
confidence: 99%
“…In [55], the stable limit cycle has been observed in autocatalytic systems through the characteristics of the Hopf bifurcation. In, [56], the exhibition of limit cycling oscillations has been observed in Biological Oscillators having both positive and negative feedbacks. The authors, [57], have observed in natural systems a closed loop as in a stable limit cycle through reviewing empirical dynamic modelling.…”
Section: Introductionmentioning
confidence: 99%